THE ROLE OF INSPIRATIONAL LEADERSHIP IN ENHANCING ORGANIZATIONAL COMMITMENT AMONG WORKING INDIVIDUALS AT TIKRIT UNIVERSITY: AN APPLIED STUDY (World Economics and Finance Bulletin, 2022)
The research dealt with the study of the role of inspirational leadership in enhancing organizational commitment among individuals working at Tikrit University. Through a random sample of individuals working at the university in question, which numbered (72) individuals distributed over the different faculties of the university. Where the research reached a set of conclusions, the most important of which is the validity of the research hypotheses, as well as the existence of a significant statistically significant effect of the inspiring leadership by removing it (self-confidence, future vision, and recognition of the leader as a tool for change ).